ANALISIS POTENSI DAN PENILAIAN INDEKS KESESUAIAN WISATA PANTAI LUMINTANG DI DESA BENTENAN KECAMATAN PUSOMAEN KABUPATEN MINAHASA TENGGARA - Lagarense, Bet El; Tatali, Aldy; Rako, Marlove E. C. (Jurnal Ilmu Pariwisata, 2023)
Lumintang Beach is a beach tourism that offers a very charming sea view and very beautiful white sand mixed with black so that it has its own attraction for visitors who come, however, marine tourism at Lumintang Beach has not been managed optimally, for this reason, it is necessary Research was conducted to analyze the potential and calculate the marine tourism suitability index at Lumintang Beach. The aim of this research is to measure the suitability index and analyze the potential for marine tourism at Lumintang Beach. The type of research used is a combination method or mixed method between qualitative and quantitative. Data collection techniques in this research are observation, interviews and documentation. The results obtained in this research provide opportunities for development which can be seen from the results of calculating the suitability of tourism for snorkeling, diving, fishing fishing and seagrass tourism. Lumintang Beach is very suitable and suitable for diving tourism, snorkeling tourism, seagrass tourism, fishing tourism and has the potential to become a marine tourism area.